2023
DOI: 10.1038/s41467-023-40151-x
|View full text |Cite
|
Sign up to set email alerts
|

Affinity-matured homotypic interactions induce spectrum of PfCSP structures that influence protection from malaria infection

Abstract: The generation of high-quality antibody responses to Plasmodium falciparum (Pf) circumsporozoite protein (PfCSP), the primary surface antigen of Pf sporozoites, is paramount to the development of an effective malaria vaccine. Here we present an in-depth structural and functional analysis of a panel of potent antibodies encoded by the immunoglobulin heavy chain variable (IGHV) gene IGHV3-33, which is among the most prevalent and potent antibody families induced in the anti-PfCSP immune response and targets the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 62 publications
(100 reference statements)
1
14
0
Order By: Relevance
“…A most revealing observation from our structure is the presence of affinity-matured antibody-antibody homotypic interactions in the context of recognizing repetitive tandem glutamate residues present across the Pf proteome. The finding that B1E11K targets a repetitive epitope whilst engaging in affinity-matured homotypic interactions is similar to how Abs elicited against repetitive elements of CSP can also bind through homotypic interactions (12) (14) (15) (13) (16) (19) (54) (17) (18) (11). We have previously shown that B cells expressing B cell receptors (BCRs) interacting via homotypic interactions activate more robustly in comparison to B cells that have mutated BCRs that disrupt this interaction (12).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…A most revealing observation from our structure is the presence of affinity-matured antibody-antibody homotypic interactions in the context of recognizing repetitive tandem glutamate residues present across the Pf proteome. The finding that B1E11K targets a repetitive epitope whilst engaging in affinity-matured homotypic interactions is similar to how Abs elicited against repetitive elements of CSP can also bind through homotypic interactions (12) (14) (15) (13) (16) (19) (54) (17) (18) (11). We have previously shown that B cells expressing B cell receptors (BCRs) interacting via homotypic interactions activate more robustly in comparison to B cells that have mutated BCRs that disrupt this interaction (12).…”
Section: Discussionmentioning
confidence: 57%
“…Protective Abs elicited against CSP primarily target this immunodominant repeat region. A large proportion of these Abs engage in homotypic interactions which are characterized by direct interactions between two antibodies’ variable regions when bound to adjacent repetitive epitopes (11) (12) (13) (14) (15) (16) (17) (18) (19). Such interactions have been demonstrated to augment B cell activation and contribute to shaping the humoral response to CSP (12).…”
Section: Introductionmentioning
confidence: 99%
“…This was unexpected given that the long version of the homologous peptide and CSP contain more repeats of the same epitopes present in the short peptide. However, it could be that the multiple tetramers in the NPNA6 peptide may allow for certain antibodies to bind via multivalent avidity 20 , 39 42 , resulting in slow dissociation with k off estimates that were limited to 10 −5 s −1 , the lowest k off to be accurately determined during data analysis. Because these antibodies were excluded from correlation analyses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…mAbs from a lineage reported to bind CSP with Fab–Fab homotypic interactions are indicated (black circles, AB-000399 (refs. 41 , 42 ), AB-007159, AB-007160, AB-007161). …”
Section: Resultsmentioning
confidence: 99%
“…Homotypic targeting is a fundamental biological concept where cells preferentially interact or bind with cells of similar or identical types 15 . This homophilic specificity is crucial in various physiological processes, including cell adhesion, tissue formation, and immune responses 69 . In therapeutic development, especially in targeted drug delivery, homotypic targeting is important in ensuring that drugs are delivered primarily to target cells, reducing systemic side effects and increasing treatment efficacy 5,1013 .…”
mentioning
confidence: 99%